Implementation of Halal Principles and Environmental Ethics in the Production Rambak Crackers at UD. Farid Jaya, Kauman Village, Mojokerto Regency. - Hasanah, Alfi Nur; Lestari, Putri Catur Ayu (Universitas Mohammad Husni Thamrin, 2026)
Indonesia is a country with the largest Muslim population in the world, so the need for product halal assurance is very important in people's consumption activities. Although halal principles and environmental ethics have received increasing attention in various studies, research that specifically examines the simultaneous implementation of these two aspects in Micro, Small, and Medium Enterprises (MSMEs) within the rambak cracker industry is still limited. This study aims to analyze the implementation of halal principles and environmental ethics in the production process of rambak crackers at UD. Farid Jaya, Kauman Village, Mojokerto Regency. This research employs a qualitative approach with a field research design. The research informants consist of the business owner, employees, and consumers selected using a purposive sampling technique. Data were collected through observation, interviews, and documentation, and then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that UD. Farid Jaya has implemented halal principles at all stages of production, starting from the selection of raw materials, processing, to packaging, supported by halal certification ownership. In addition, the implementation of environmental ethics is reflected in responsible waste management and compliance with environmental permits. This study recommends that MSME actors maintain consistency in implementing halal principles and environmentally friendly practices, while the government should enhance assistance in developing sustainable production.